2011
DOI: 10.1016/j.bcp.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 deactivation enhances cytoplasmic Nur77 expression level and improves the apoptotic effect of fenretinide in human liver cancer cells

Abstract: Fenretinide, a synthetic retinoid, is a promising anticancer agent based on many in vitro, animal, and chemoprevention clinical trial studies. However, cells such as HepG2 human liver cancer cells are resistant to the apoptotic effect of fenretinide. Previously, we have shown that fenretinideinduced apoptosis is Nur77 dependent, and the sensitivity of the cancer cells to fenretinideinduced apoptosis is positively associated with cytoplasmic enrichment of Nur77. The goal of current study was to identify means t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…TR3 suppresses Wnt signalling activity thereby suppressing intestinal tumourigenesis . Many groups of scientist reported it as a potential therapeutic target due to its tumour suppressive effect on various types of cancer …”
Section: Discussionsupporting
confidence: 65%
“…TR3 suppresses Wnt signalling activity thereby suppressing intestinal tumourigenesis . Many groups of scientist reported it as a potential therapeutic target due to its tumour suppressive effect on various types of cancer …”
Section: Discussionsupporting
confidence: 65%
“…Nur77 post-translational modification studies have shown that ERK1/2 phosphorylation promoted nuclear localization of Nur77, whereas Chk2 phosphorylation led to nuclear export (16, 32). RXRα as well as RARβ also regulate Nur77-dependent apoptotic pathways by forming a complex with Nur77 (15, 25).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (EGF) and other mitogens rapidly and potently induce the expression of nuclear Nur77, which serves as a transcription factor to enhance cell survival (14). The apoptotic effect of cytosolic Nur77 has also been studied using apoptosis inducers (15, 16). In the cytosol, Nur77 unmasks the BH-3 domain of Bcl-2, converting Bcl-2 into a pro-apoptotic molecule (12).…”
Section: Introductionmentioning
confidence: 99%
“…Many pro-apoptotic agents and stimuli have been reported to be associated with nuclear export and translocation of NR4A1 [17, 33]. Apoptosis induced in hepatocellular carcinoma cells by retinoids have been demonstrated to be NR4A1 dependent and to be associated with localization of NR4A1 in the mitochondria [34]. In androgen sensitive LNCaP adenocarcinoma cells several apoptosis inducers consistently caused mitochondrial localization of NR4A1, and mutants that lacked mitochondrial localization failed to induce apoptosis [33].…”
Section: Discussionmentioning
confidence: 99%